Representasi Kepribadian Tokoh Utama dalam Novel Mata dan Nyala Api Purba karya Okky Madasari: Kajian Psikologi Erich Fromm - Nur Farida Maulidya; Hespi Septiana (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This study aims to describe the psychological conflicts experienced by the main character in the novel Mata and Nyala Api Purba. The theory used in this study is personality psychology from Erich Fromm. The research method used is a qualitative descriptive method with a literary psychology approach. The source of the data in this study is the novel Mata and Nyala Api Purba by Okky Madasari. The research data is presented in the form of text excerpts that represent personality for the activities, dialogues, and actions performed by the main character in personality psychology, Erich Fromm. Data collection uses reading and note techniques combined with objective analysis techniques. The results of this study indicate that there are (1) existential dilemmas including humans as animals and humans as humans, life and death, imperfection and perfection, solitude and togetherness; (2) the need for freedom and attachment includes the need for connectedness, rootedness, being a creator, unity, identity; (3) the need to understand and act includes the need for an orientation framework, a loyalty framework, arousal-stimulation, effectiveness; and (4) the mechanism of escape includes authoritarianism, destruction, and adjustment that occurs in the character Matara as the main character in the novel Mata and Nyala Api Purba.